Helmet Continuous Positive Airways Pressure (CPAP) treatment in a Non-Small Cell Lung Cancer (NSCLC) patient with severe hypoxemic respiratory failure due to gemcitabine therapy - Graziani, Alessandro; Tamberi, Stefano; Papiani, Giorgio; Mirici Cappa, Federica; Casalini, Pierpaolo; Foschi, Giuseppe Francesco (European Journal of Oncology and Environmental Health, 2017)
Gemcitabine is a pyrimidine analogue used worldwide for many solid tumours such as pancreatic cancer, ovarian cancer, non small cell lung cancer (NSCLC) and breast cancer. In this case report, we describe a patient who was treated with gemcitabine for NSCLC (poor differentiated squamous cell carcinoma) and who subsequently developed a severe respiratory failure with a radiological pattern of interstitial pneumoniae. Discontinuation of the drug, administration of corticosteroids and respiratory support are the mainstays of the treatment. Helmet Continuous Positive Airways Pressure (CPAP) allowed a prolonged, comfortable and safe treatment of the patient until the resolution of the acute respiratory failure. We think that helmet-CPAP could be a useful tool, even outside of intensive care unit, for the treatment of patients with severe interstitial pneumoniae due to gemcitabine therapy.